Sickle Cell Disease in Children - Meier, Emily Riehm (2012)
Early identification of infants with sickle cell disease (SCD) by newborn screening, now universal in all 50 states in the US, has improved survival, mainly by preventing overwhelming sepsis with the early use of prophylactic penicillin. Routine transcranial Doppler screening with the institution of chronic transfusion decreases the risk of stroke from 10% to 1% in paediatric SCD patients. Hydroxyurea decreases the number and frequency of painful crises, acute chest syndromes and number of blood transfusions in children with SCD. Genetic research continues to be driven toward the prevention and ultimate cure of SCD before adulthood. This review focuses on clinical manifestations and therapeutic strategies for paediatric SCD as well as the evolving topic of gene-focused prevention and therapy.